Facile synthesis of hierarchical micro-mesoporous HKUST-1 by a mixed-linker defect strategy for enhanced adsorptive removal of benzothiophene from fuel. (15th September 2021) - Guo, Liying; Du, Jinghua; Li, Chengbin; He, Gaohong; Xiao, Yonghou
Graphical abstract: Highlights: A mixed-linker defect strategy was proposed to construct a bimodal pore HUKST-1. Defective HKUST-1 could be rapidly obtained under microwave conditions. Adsorption desulfurization performance of defective HKUST-1 is obviously enhanced. Defective HKUST-1 expose more adsorptive sites and facilitate benzothiophene diffusion. OH-HKUST-1-0.2 exhibits excellent adsorption and regeneration for BT removal. Abstract: Developing high-efficiency adsorbents is crucial for removing aromatic sulfur containing compounds from the fossil fuels. HKUST-1 is considered as a promising candidate of adsorbents for deep desulfurization. However, the typical HKUST-1 possesses only micropores, which restricts the diffusion and limits the desulfurization capacity. Herein, we proposed a mixed-linker defect strategy to construct a bimodal micro-mesoporous HKUST-1 to enhance adsorptive removal of benzothiophene (BT) from fuels. A rapid microwave-assisted synthetic route was developed for preparing a series of micro-meso porous OH-HKUST-1 -x ( x = 0.1, 0.2 and 0.3) by adjusting the ratio of 5-hydroxyisophthalic acid to benzene-1, 3, 5-tricarboxylate acid. This series of hierarchically porous metal-organic frameworks (MOFs) features 0.7–0.8 nm and 3.4–3.8 nm micropore and mesopore, respectively. The effects of linker defects on the chemical and physical properties of the materials were systematically studied. The X-ray diffraction patterns showed that the as-synthesized OH-HKUST-1 -x containing hydroxyl defects still retained the original crystal structure. The OH-HKUST-1 -x exhibited a higher desulfurization efficiency in comparison with HKUST-1, because with increasing the mole ratio of the mixed linkers, larger pore diameters were generated. The bimodal micro-mesoporous structure facilitates adsorbates diffusion and leads to higher exposure of the unsaturated adsorptive site of Cu 2+ than the microporous structure. The as-synthesized OH-HKUST-1-0.2 displayed the best performance towards adsorptive removal of BT, the static and breakthrough adsorption capacity achieved 26.30 mg S g −1 and 0.0490 mmol g −1, respectively. Additionally, after the OH-HKUST-1-0.2 was regenerated six times it still had a desulfurization performance as 88.3% of the fresh adsorbent.